Aprendizagem social nas transições para a sustentabilidade ecocultural em larga escala: o caso do centro de saberes e cuidados socioambientais da Bacia do Prata (CSCS) - Kotz, Jair (2023)
The Thesis focuses on social learning and its relevance as a strategy for large-scale collective action in the context of transitions toward “eco-cultural sustainability”. Thus, the case of the Center for Knowledge and Socio-Environmental Care of the La Plata Basin (CSCS) can be considered as an unprecedented social learning initiative of a bioregional nature (La Plata Basin, five countries); multisectoral (government, civil society, academia, media); and multilevel (global-local). Although on paper there are many projects like this, they are rarely transferred to the “real world”. For this reason, the CSCS experience developed by five countries over seven years (2006-2012) constitutes an important reference laboratory for social learning. The thesis contrasts theory with empirical insights from stakeholders to take stock of “lessons learned” and envision a new social learning architecture that facilitates large-scale collective action in pursuit of regional sustainability. The investigation is divided into three articles. The first article addresses social learning in polycentric governance (the Latin American perspective) and presents a series of theoretical assumptions about the possible application of social learning to large-scale collective action in the context of transitions to “eco-cultural sustainability”. The second article seeks to understand the crisis and opportunity from the perspective of the Center for SocioEnvironmental Knowledge and Care of the La Plata Basin in the window of the new paradigm: it develops a multilevel timeline to analyze the impact of contextual mechanisms on the ups and downs of the CSCS. The third article focuses on synthesizing empirical insights from the CSCS stakeholders to take stock of “lessons learned” (in terms of strengths and weaknesses) during the translation of a theoretical social learning model into real-world institutional arrangements in the La Plata Basin. The Thesis opted for the methodological approach of collaborative action research, and it is concluded that the CSCS as a bioregional meta-governance platform requires in some way “to be able to balance the serious dilemmas and contradictions that affect its resilience”. If we follow the metaphor of CSCS as “social software” for a sense of belonging and responsibility for large-scale collective action, there are considerable “failures” that need to be resolved to avoid “operating system crashes” in the future. It can be inferred that flaws such as single funding sources have the potential to crash the operating system.